Cruelty to Children and its Complications (Res Medica, 2014)
A dissertation read before the Society on Friday, 24th February, 1967.The concept of what constitutes cruelty to children is best described in the Children and Young Persons Act as “Assault, ill-treatment, neglect, abandonment or exposure such as will cause unnecessary suffering or injury to health, including any mental derangement.”